2017
DOI: 10.1371/journal.pone.0171697
|View full text |Cite
|
Sign up to set email alerts
|

Within-season variability of fighting behaviour in an Australian alpine grasshopper

Abstract: Throughout the breeding season, changing environmental and biological conditions can lead to variation in the reproductive landscape of many species. In alpine environments temperature is a key driver of behaviour for small ectotherms such as insects, but variable biotic factors such as mate quality and availability can also influence behaviour. Kosicuscola tristis is a small semelparous grasshopper of the Australian alpine region. In a rare behaviour among grasshoppers, K. tristis males engage in vigorous fig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 90 publications
(127 reference statements)
0
18
0
Order By: Relevance
“…In previous studies, we have found that females reject males in up to 30% of trials and show aggression in up to 10% of trials (Muschett et al, ). Previous observations have also revealed evidence of females rejecting males by kicking and grappling with the male (Muschett et al, ). However, we did not observe female mate rejection in our experiments.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…In previous studies, we have found that females reject males in up to 30% of trials and show aggression in up to 10% of trials (Muschett et al, ). Previous observations have also revealed evidence of females rejecting males by kicking and grappling with the male (Muschett et al, ). However, we did not observe female mate rejection in our experiments.…”
Section: Discussionmentioning
confidence: 80%
“…At last, it is likely that the prevalence of male choice varies throughout the breeding season. Muschett et al () determined male K. tristis become more aggressive towards each other at the end of the breeding season, as opportunities to mate dwindle. An assessment of the seasonal variability of this behaviour would provide much‐needed insight into the mechanisms of male choice in this species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations